2022
DOI: 10.3390/microorganisms10020462
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Application of Bio-Compost Increased Soil Microbial Community Diversity and Altered Its Composition and Network

Abstract: The influence of bio-compost on the diversity, composition and structure of soil microbial communities is less understood. Here, Illumina MiSeq sequencing and a network analysis were used to comprehensively characterize the effects of 25 years of bio-compost application on the microbial diversity of soil and community composition. High dosages of bio-compost significantly increased the bacterial and fungal richness. The compositions of bacterial and fungal communities were significantly altered by bio-compost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
(65 reference statements)
7
19
0
Order By: Relevance
“…Our results showed that in comparison with the control, compost fertilization significantly increased the fungal richness and diversity indices at S1, while bacterial richness and diversity indices were significantly decreased at S1 and S3. In agreement with our findings, Liu et al [ 12 ] and Azeem et al [ 9 ] reported that compost application decreased soil bacterial diversity. Similarly, Gao et al [ 37 ] and Luo et al [ 41 ] found that the addition of organic fertilizers such as biochar increased soil fungal diversity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results showed that in comparison with the control, compost fertilization significantly increased the fungal richness and diversity indices at S1, while bacterial richness and diversity indices were significantly decreased at S1 and S3. In agreement with our findings, Liu et al [ 12 ] and Azeem et al [ 9 ] reported that compost application decreased soil bacterial diversity. Similarly, Gao et al [ 37 ] and Luo et al [ 41 ] found that the addition of organic fertilizers such as biochar increased soil fungal diversity.…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, Sharaf et al [ 39 ] also suggested that bacterial abundance increased under compost amendment in the apple rhizosphere. Moreover, Liu et al [ 12 ] reported that long-term application of biocompost increased soil fungal abundance. On the other hand, our findings are in discordance with the results by Azeem et al [ 9 ], who found that amending turfgrass soils with biochar and compost did not affect bacterial 16S rRNA gene and fungal ITS rDNA region copy numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal cycling program of the PCR reaction process included an initial denaturation step at 98 °C for 1 min, followed by 30 cycles of denaturation at 98 °C for 10 s, annealing at 50 °C for 30 s, extension at 72 °C for 30 s, and then a final 5-min extension at 72 °C. PCR reactions were subjected to three replicates [ 28 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of Chao1 and ACE revealed that soil treatment with inorganic fertilizers can significantly reduce soil bacterial richness than that with the no soil treatment. Similarly, Liu et al (2022) reported increase in Shannon diversity index and richness index of the microbial community of soil under application of biological compound fertilizers for 25 years. Kirchmann et al (2013) found that the application of inorganic and organic fertilizers had no significant effect on the bacterial and fungal Shannon diversity index as compared to the control soil as reported in the 10.…”
Section: Discussionmentioning
confidence: 85%